Case Report: A report on the countermeasures after PICC line breakage in 3 postoperative breast cancer patients - Jing, Yuqin; Qu, Jing; Jiang, Shuo; Wang, Xiaomin (Frontiers in Surgery, 2024)
Peripherally inserted central catheter (PICC) is a widely used technique in oncology chemotherapy, characterized by safety, reliability, and long dwell time. However, a catheter can break due to various causes. When an acute rupture occurs, it always lead to sever complications which may threaten patients' safety and potentially result in medical disputes. In this study, we collected and analyzed 3 cases of PICC line breakage causing drug leakage in our hospital from 2018 to 2023. All these 3 cases were postoperative breast cancer patients accepting chemotherapy, with 2 cases involving external partial breakage and 1 case involving internal partial breakage.Due to timely and appropriate management, no acute rupture occurred. We propose some ideas such as selecting high-quality catheter materials and avoiding over extension or repeated bending are crucial in preventing PICC line breakage. In addition, we also recommend establishing a standardized and scientific management pattern of PICC to ensure the safety and effectiveness of its clinical application, including comprehensive assessment, "four-element" intervention, and continuous evaluation.